Own and perceived parental religiosity and the quality of the parent-child relationship - Fredericks, Farah (Journal of beliefs and values, 2015)
This aim of this study was to investigate the association between perceived parental religiosity and the quality of the parent-child relationship. Eighty-nine adolescent boys and girls completed the Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ) and the Parent-Child Relationship Survey (PCRS). The results showed that the girls had a better relationship with their mothers than with their fathers, while the boys tended to view their relationships with their father and mother of equal quality. It was also found that greater perceived religiosity of both the fathers and mothers was associated with a better parent-child relationship.